Improved forage grasses: Bringing their integration into humid- to sub-humid livestock production systems to scale - Sibiko, Kenneth W; Odhiambo, Ruth; Muthomi, Fredrick; Kipkosgei, Solomon; Mwema, Emmanuel; Hansen, Andreas; Mwendia, Solomon; Notenbaert, An (2024)
The closing workshop for the Grass 2 Cash @scale project organised in Kisumu, Kenya between the 27th and 28th of June 2024. It was a 2-day physical meeting with 26 participants from CIAT, KALRO, Ripple Effect, Advantage Crops Ltd, the Department of Livestock (Kakamega), dairy cooperatives, forage business groups/CBOs, extension trainers, and men, women and youth farmers from Meru, Uasin-Gishu, Kakamega, Bungoma, Busia and Siaya counties of Kenya. The objectives of the workshop were: 1) to create a common understanding of the research problem, project’s objectives, and components; 2) to reflect on the project’s theory of change and share the achievements realized in the project; 3) to share insights from the project evaluation and other research studies; and 4) to discuss challenges encountered and suggest ways to improve the implementation of similar ongoing or future projects.